2021
DOI: 10.4103/ijnmr.ijnmr_22_20
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Moral Sensitivity, Ethical Climate, and Job Strain with Patient Privacy from Viewpoint of Operating Room Staffs

Abstract: Background: The privacy of patients in the operating room is in particular importance. The results of previous studies have shown that various factors are affecting in this context. The aim of this study is to evaluate the relationship between moral sensitivity, ethical climate, and job strain with respect to patients' privacy in operating rooms. Materials and Methods: All of operating rooms nurses of teaching hospitals affiliated to Ardabil University of Medical Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…It has been observed that there is a positively and significant relationship between the moral sensitivity of nurses and patient privacy and that this is a more predictor variable for patient privacy than others. 7 In addition, in a study conducted with student nurses, it was shown that the behaviors of trainee nurses to protect patient privacy were significantly positively related to patient privacy protection cognition, moral sensitivity and empathy. 33…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that there is a positively and significant relationship between the moral sensitivity of nurses and patient privacy and that this is a more predictor variable for patient privacy than others. 7 In addition, in a study conducted with student nurses, it was shown that the behaviors of trainee nurses to protect patient privacy were significantly positively related to patient privacy protection cognition, moral sensitivity and empathy. 33…”
Section: Discussionmentioning
confidence: 99%
“…6 Privacy in care practices has physical, social, psychological and cognitive aspects. 7 The absence of direct intervention on the patient's body is an example of physical privacy; the patient's control over the parties, frequency and duration of interpersonal relationships is an example of social privacy. Psychological privacy is the process of controlling one's cognition, mood, shaping values and protecting individual identity.…”
Section: Anah Tar Ke LI Me Ler: Hemşirelik; Etik; Hasta Mahremiyeti; ...mentioning
confidence: 99%
See 1 more Smart Citation
“…46 A separate study suggested a correlation between the moral awareness of operating room nurses and ethical conduct. 47 Based on our research, participants associated ethical conduct with professionalism rather than moral behavior. However, there is a lack of research on ethical dilemmas during earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that utilised the HECS (n = 43) were geographically diverse. The majority of studies were carried out in Iran (n = 13) 2 20,21,22,23,24,25,26,27,28,29,30,31,32 and the US (n = 10). [33][34][35][36][37][38][39][40][41][42] Several studies were carried out in Asia (n = 11) 10,[43][44][45][46][47][48][49][50][51] and Europe (n = 6).…”
Section: Hospital Ethical Climatementioning
confidence: 99%